Discovery of the genus Loeblites Franz (Coleoptera: Staphylinidae: Scydmaeninae) in China, with description of a new species - Zhou, De-Yao; Li, Li-Zhen (Zootaxa, 2015)
Loeblites chinesis sp. n. (Scydmaeninae: Cyrtoscydmini) from Yunnan, southern China is described, and its important diagnostic characters are illustrated. This species represents the first record of Loeblites in China. A single female of Loeblites from Tengchong, Yunnan is also recorded. It is similar to Loeblites mastigicornis from Thailand in general habitus and form of the spermatheca, but the identity of this species remains unconfirmed until males are found.